METHODOLOGY FOR ASSESSING THE LEVEL OF TRAIN SAFETY - Abdazimov, Shavkat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. The results of the analysis of the existing methods of train safety management show that these methods are not enough to solve the issues of economic traffic safety management. This means that there is a need to develop a methodology to improve the efficiency of traffic safety management. This article presents a newly developed new methodology for assessing the level of safety of train traffic, in which the formula for determining the level of safety of cargo transportation is developed taking into account the correction factor, taking into account the number of crashes, accidents, defects in operation and other incidents, the standard of the level of safety of vehicles and the severity of individual cases of safety violations.